Analisis Sistem Informasi Akuntansi Penjualan Pada Apotek “ Z “ - Ovin Liviana Bela; Amin Sadiqin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The benefit of this research is that the author analyzes whether the sales accounting information system implemented at the "Z" pharmacy is in accordance with the current accounting information system procedures in processing sales made so far. This study uses a qualitative descriptive method in analyzing. In this study, the data collection method used was by conducting observations, interviews, participatory, and direct documentation at the pharmacy "Z" directly to the pharmacy owner and to the pharmacy employees. From the results of this study, the analysis of sales and purchase accounting information systems found in these pharmacies is still a lot of lag or not according to accounting information system procedures, where the sales system carried out by pharmacies is still manual or conventional. In addition, in the internal control system there are still deficiencies or not yet effective and the design of the SIA which consists in the division of tasks is not in accordance with the organizational structure.